Preparation method and application of sulfur-resistant cheap demercuration adsorbent
By preparing a pyrolysis coke adsorbent based on waste tires, the problems of low efficiency and poor sulfur resistance of activated carbon injection technology in removing Hg0 from stationary source flue gas were solved, achieving a high-efficiency and low-cost mercury capture effect.
Patent Information
- Application Number
- CN202511202370.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2026-01-16
AI Technical Summary
Existing activated carbon injection technology is inefficient, has poor sulfur resistance, and is costly when removing Hg0 from stationary source flue gas, making it difficult to meet the demand for efficient and low-cost mercury removal.
Using waste tires as raw materials, a pyrolytic coke adsorbent with a large number of sulfur-containing active sites is prepared through pyrolysis temperature, gas composition and activated coke treatment. Combined with inert atmosphere and chemical reagent treatment, the sulfur resistance and adsorption capacity are improved.
A low-cost, sulfur-resistant, and high-adsorption-capacity pyrolysis coke adsorbent was developed, which effectively captures gaseous mercury and significantly improves mercury removal efficiency and sulfur resistance.
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorbent preparation technology, and in particular to a method for preparing and applying a sulfur-resistant, inexpensive mercury-removing adsorbent. Background Technology
[0002] Mercury, commonly known as quicksilver, with the chemical symbol Hg, is a heavy metal that exists in both gaseous and liquid forms at room temperature. Mercury and its compounds are widely found in the natural environment, such as in rocks, sediments, and minerals, primarily in the form of cinnabar (HgS). Mercury exhibits long-distance migration and bioaccumulation, and can be converted into highly toxic methylmercury in nature, posing a significant threat to the environment and human health. Mercury exists in flue gas primarily in three forms: gaseous elemental mercury (HgS). 0 ), gaseous mercury oxide (Hg) 2+ ) and particulate mercury (Hg p In the atmospheric environment, mercury is mainly present as Hg. 0 Mercury exists in various forms and can remain in the atmosphere for months to a year, being transported long distances by air currents, causing mercury pollution in areas far from the pollution source and resulting in serious health and economic losses. Therefore, mercury and its compounds have received widespread attention from researchers as global pollutants.
[0003] Currently, over 99% of Hg p It can be removed by dust removal equipment, with more than 80% of Hg removed. 2+ It can be removed by wet desulfurization equipment, but Hg 0 It is difficult for pollution control equipment to directly capture it. In stationary source flue gas, Hg 0 It accounts for approximately Hg of flue gas T 20%-50%, Hg 0 It can account for over 90% of total mercury emissions. Therefore, Hg 0 Mercury removal is a crucial aspect of addressing mercury pollution emissions from coal-fired power plants. Activated carbon injection (ACI) is the most mature flue gas adsorption technology for mercury removal and is widely used in the treatment of mercury pollution in coal-fired power plants. The excellent pore structure and abundant oxygen-containing functional groups on the surface of activated carbon provide numerous physical and chemical adsorption sites for mercury adsorption, promoting the enrichment and adsorption of mercury from flue gas on its surface. However, the low adsorption efficiency and capacity, poor sulfur resistance, and high cost of activated carbon limit its application. Therefore, it is essential to find an alternative adsorbent that is inexpensive, has good sulfur resistance, and high adsorption performance.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] This invention addresses the problems of poor sulfur resistance, low adsorption capacity, and high cost of mercury adsorbents for stationary source waste gas. It innovatively develops a preparation method based on precise control of the pyrolysis preparation temperature, flue gas composition, and cleaning and impurity removal of pyrolyzed waste tires, and develops a pyrolyzed tire activated coke adsorbent with good sulfur resistance, high adsorption capacity, and low cost.
[0006] The purpose of this invention is to provide a method for preparing an inexpensive, sulfur-resistant, and highly efficient flue gas elemental mercury adsorbent to meet the requirements of efficient capture of gaseous mercury in stationary source exhaust gas.
[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for preparing an adsorbent, comprising: pyrolyzing waste tires in an inert gas atmosphere at 550-650°C; wherein the inert gas atmosphere is a pure inert gas atmosphere or an inert gas atmosphere containing SO2 gas.
[0008] This invention utilizes waste tires as pyrolysis raw materials and, through research on pyrolysis temperature, gas composition, and activated coke treatment methods, develops a pyrolysis coke adsorbent with a large number of sulfur-containing active sites. The pyrolysis coke exhibits good sulfur resistance, high adsorption capacity, and low cost.
[0009] According to the method for preparing an adsorbent of the present invention, the content of SO2 gas in the inert gas atmosphere containing SO2 gas is 0.1% to 1%.
[0010] According to the method for preparing an adsorbent of the present invention, when the inert gas atmosphere is a pure inert gas, the method further includes an activation treatment; when the inert gas atmosphere is an inert gas containing SO2 gas, the activation treatment is not performed.
[0011] According to the method for preparing an adsorbent according to the present invention, the activation treatment includes: impregnating the pyrolysis product with one or more of water, ethanol and carbon disulfide, and then subjecting it to ultrasonic treatment.
[0012] According to the method for preparing an adsorbent according to the present invention, during the impregnation process, the solid-liquid ratio is controlled to be 1:(4~6) in g / mL.
[0013] According to the method for preparing an adsorbent according to the present invention, the impregnation treatment time is 0.5~1.5h.
[0014] According to the method for preparing an adsorbent according to the present invention, the ultrasonic treatment power is 800~1200W and the ultrasonic treatment time is 5~15min.
[0015] A method for preparing an adsorbent according to the present invention includes either method one or method two: Method 1: Waste tires are crushed to 8-10 mm, and then heated from room temperature to 550-650°C at a heating rate of 15-25°C / min under a nitrogen atmosphere, and held at this temperature for 0.5-1.5 hours to obtain the first pyrolysis coke; the first pyrolysis coke is impregnated with one or more of water, ethanol, and carbon disulfide, and after impregnation, it is ultrasonically treated, and then dried at 100-200°C; wherein the impregnation treatment time is 0.5-1.5 hours, the ultrasonic treatment power is 800-1200W, and the ultrasonic treatment time is 5-15 minutes. or, Method 2: Waste tires are crushed to 8-10 mm and then pyrolyzed at a heating rate of 15-25 °C / min from room temperature to 550-650 °C in a nitrogen atmosphere containing 0.1%-1% SO2 gas and held at that temperature for 0.5-1.5 h.
[0016] Secondly, the present invention provides an adsorbent prepared by the above-described preparation method.
[0017] Thirdly, the present invention provides the application of the above-mentioned adsorbent in mercury removal and sulfur resistance.
[0018] Based on this, the technical solution of the present invention has the following beneficial effects: The adsorbent, its preparation method, and its application provided by this invention use waste tire particles as pyrolysis raw material. Through research on pyrolysis temperature, gas composition, and activated coke treatment methods, a pyrolysis coke adsorbent with a large number of sulfur element active sites has been developed. The pyrolysis coke has the characteristics of good sulfur resistance, high adsorption capacity, and low price. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0020] Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0021] Example 1 This embodiment provides an adsorbent, the preparation method of which includes the following steps: Shred the waste tires to 8-10 mm, and place 5 g of the shredded waste tires into a pyrolysis furnace. Heat at 200 mL / min. -1Under N2 environment, the pyrolysis furnace operates at 20℃·min -1 The heating rate was increased from room temperature to 500°C, and then maintained at 600°C for 1 hour. The mixture was then cooled to room temperature under a nitrogen atmosphere to obtain pyrolytic tire activated coke, which was named T5N.
[0022] Example 2 This embodiment provides an adsorbent, the preparation method of which includes the following steps: Shred the waste tires to 8-10 mm, and place 5 g of the shredded waste tires into a pyrolysis furnace. Heat at 200 mL / min. -1 Under N2 environment, the pyrolysis furnace operates at 20℃·min -1 The heating rate was increased from room temperature to 600°C, and then maintained at 600°C for 1 hour. The mixture was then cooled to room temperature under a nitrogen atmosphere to obtain pyrolytic tire activated coke, which was named T6N.
[0023] Example 3 This embodiment provides an adsorbent, the preparation method of which includes the following steps: Shred the waste tires to 8-10 mm, and place 5 g of the shredded waste tires into a pyrolysis furnace. Heat at 200 mL / min. -1 Under N2 environment, the pyrolysis furnace operates at 20℃·min -1 The heating rate was increased from room temperature to 700°C, and then maintained at 600°C for 1 hour. The mixture was then cooled to room temperature under a nitrogen atmosphere to obtain pyrolytic tire activated coke, which was also named T7N.
[0024] Example 4 This embodiment provides an adsorbent, the preparation method of which includes the following steps: Waste tires were shredded to 8-10 mm and then pyrolyzed under SO2+N2 conditions. Specifically, 5 g of shredded waste tires were placed in a quartz reactor, oxygen was removed with nitrogen (N2), and then nitrogen containing 0.1% SO2 was continuously introduced at a flow rate of 200 mL / min. The heating rate was 20 °C / min, and the temperature was raised to 600 °C. The temperature was then maintained at 600 °C for 1 hour, and finally cooled to room temperature. The resulting pyrolytic coke was denoted as T6N0.1S.
[0025] Example 5 This embodiment provides an adsorbent, the preparation method of which includes the following steps: Waste tires were shredded to 8-10 mm and then pyrolyzed under SO2+N2 conditions. Specifically, 5 g of shredded waste tires were placed in a quartz reactor, oxygen was removed with nitrogen (N2), and then nitrogen containing 1% SO2 was continuously introduced at a flow rate of 200 mL / min. The heating rate was 20 °C / min, and the temperature was raised to 600 °C. The temperature was then maintained at 600 °C for 1 hour, and finally cooled to room temperature. The resulting pyrolytic coke was denoted as T6N1S.
[0026] Example 6 This embodiment provides an adsorbent, the preparation method of which includes the following steps: The T6N obtained in Example 2 was impregnated with deionized water at a solid-liquid ratio of 1 g: 5 mL for 1 h, followed by ultrasonic treatment for 10 min at a power of 1000 W, and then dried at 150 °C. The resulting sample was labeled as T6NH2O.
[0027] Example 7 This embodiment provides an adsorbent, the preparation method of which includes the following steps: The T6N obtained in Example 2 was impregnated with ethanol at a solid-liquid ratio of 1 g: 5 mL for 1 h, then ultrasonically treated for 10 min at a power of 1000 W, and then dried at 150 °C. The resulting sample was labeled as T6NC2H6O.
[0028] Example 8 This embodiment provides an adsorbent, the preparation method of which includes the following steps: The T6N obtained in Example 2 was impregnated with carbon disulfide at a solid-liquid ratio of 1 g: 5 mL for 1 h, followed by ultrasonic treatment for 10 min at a power of 1000 W, and then dried at 150 °C. The resulting sample was labeled as T6NCS2.
[0029] Example 9 This embodiment provides an adsorbent, the preparation method of which includes the following steps: The T6N1S obtained in Example 5 was treated with deionized water at a solid-liquid ratio of 1 g: 5 mL for 1 h, followed by ultrasonic treatment for 10 min at a power of 1000 W, and then dried at 150 °C. The resulting sample was labeled as T6N1SH2O.
[0030] Example 10 This embodiment provides an adsorbent, the preparation method of which includes the following steps: The T6N1S obtained in Example 5 was treated with ethanol at a solid-liquid ratio of 1 g: 5 mL for 1 h, followed by ultrasonic treatment for 10 min at an ultrasonic power of 1000 W, and then dried at 150 °C. The resulting sample was labeled as T6N1SC2H6O.
[0031] Example 11 This embodiment provides an adsorbent, the preparation method of which includes the following steps: The T6N1S obtained in Example 5 was treated with carbon disulfide at a solid-liquid ratio of 1 g: 5 mL for 1 h, followed by ultrasonic treatment for 10 min at a power of 1000 W, and then dried at 150 °C. The resulting sample was labeled as T6N1SCS2.
[0032] Experimental Example 1 At N2+6%O2, 100000 h -1 air velocity and 80.0 μg·m -3 The adsorption efficiency of T5N, T6N and T7N activated carbon was tested under elemental mercury concentration conditions.
[0033] The results showed that the initial mercury adsorption efficiency of T6N reached 88.3%, and remained above 66.3% after 300 min, with an adsorption capacity of 406 µg / g, exceeding the adsorption capacity of commercial adsorbent activated carbon (283.7-344.3 µg / g). This indicates that T6N exhibits good mercury adsorption performance.
[0034] The initial mercury removal efficiency of activated carbons T6N0.1S and T6N1S reached 100%. After 300 min, the efficiency of activated carbons T6N0.1S and T6N1S remained above 90% and 95%, respectively, indicating that SO2 promoted the formation of adsorption sites during the pyrolysis process. The adsorption capacity exceeded 800 µg / g and 4000 µg / g, respectively, which greatly improved the elemental mercury capture performance of activated carbons T6N0.1S and T6N1S.
[0035] Experiment Example 2 At N2 + 6% O2 + 100 / 300 / 500 ppm SO2, 100000 h -1 air velocity and 80.0 μg·m -3 The adsorption efficiency of T6N and T6N1S activated carbon was tested under elemental mercury concentration conditions.
[0036] The results showed that T6N exhibited an initial mercury adsorption efficiency exceeding 85% under SO2 concentrations of 100 ppm, 300 ppm, and 500 ppm, and maintained above 60%, 50%, and 60% respectively after 300 min. This indicates that T6N demonstrates certain sulfur resistance. High concentrations of SO2 promoted the adsorption capacity of elemental mercury, possibly because SO2... - It reacts with SO2 to form a certain amount of elemental sulfur, which promotes the adsorption performance of elemental mercury.
[0037] The initial mercury removal efficiency of activated carbon T6N1S reached over 100%, 90%, and 99% under SO2 conditions of 100 ppm, 300 ppm, and 500 ppm, respectively. After 300 min, the efficiency of T6N1S activated carbon remained above 90%, 65%, and 60%, respectively, indicating that low concentrations of SO2 had little impact on the elemental mercury capture performance of T6N1S activated carbon, demonstrating good adsorption performance. High concentrations of SO2 reduced the adsorption performance of T6N1S activated carbon.
[0038] Experimental Example 3 In N2 + 6% O2 + 500 ppm SO2, 100,000 h -1 air velocity and 80.0 μg·m -3 The adsorption efficiency of activated carbons T6NH2O, T6NC2H6O, T6NCS2, T6N1SH2O, T6N1SC2H6O and T6N1SCS2 was tested under elemental mercury concentration conditions.
[0039] The results showed that the removal efficiencies of T6NH2O, T6NC2H6O, and T6NCS2 remained consistently within the 80%-85% range over 300 min, indicating that surface impregnation cleaning improved the exposure of chemical sites on the adsorbent surface, thereby enhancing the adsorption capacity and sulfur resistance of the adsorbent. T6N1SH2O initially achieved 100% mercury removal efficiency, which remained above 80% after 300 min; the activated carbon adsorption efficiencies of T6N1SC2H6O and T6N1SCS2 exceeded 75%.
[0040] This invention regulates activated coke through steps such as pyrolysis temperature, flue gas composition, and chemical cleaning (deionized water, ethanol, and carbon disulfide). The final results show that T6N1S activated coke exhibits the best mercury adsorption performance under pyrolysis conditions of 1% SO2 and 600℃. Deionized water cleaning further improves the sulfur resistance of T6N1S, resulting in optimal sulfur resistance and adsorption. Activated coke directly pyrolyzed under pure N2 conditions, after deionized water cleaning, achieves good sulfur resistance and mercury removal. These methods provide feasible approaches and technologies for the reuse of waste tires and the preparation of inexpensive and efficient mercury adsorbents.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for producing an adsorbent, characterized by, The application relates to a preparation method of an adsorbent. The waste tire is pyrolyzed at 550-650 DEG C under an inert gas atmosphere; the inert gas atmosphere is a pure inert gas atmosphere or an inert gas atmosphere containing SO2 gas.
2. The method for producing an adsorbent according to claim 1, characterized by, The content of SO2 gas in the inert gas atmosphere containing SO2 gas is 0.1%-1%.
3. The method of claim 1, wherein the adsorbent is prepared by a method comprising: When the inert gas atmosphere is pure inert gas, the activation treatment is further included; when the inert gas atmosphere is inert gas containing SO2 gas, the activation treatment is not included.
4. The method of claim 3, wherein the adsorbent is prepared by a method comprising: The activation treatment includes: one or more of water, ethanol and carbon disulfide are used to impregnate the pyrolysis product, and then ultrasonic treatment is carried out.
5. The method of claim 4, wherein the adsorbent is prepared by a method comprising: During the impregnation process, the solid-liquid ratio is controlled to be 1: (4-6) in g / mL.
6. The method of claim 4, wherein the adsorbent is prepared by a method comprising: The impregnation treatment time is 0.5-1.5 h.
7. The method of claim 4, wherein the adsorbent is prepared by a method comprising: The ultrasonic treatment power is 800-1200 W, and the ultrasonic treatment time is 5-15 min.
8. The method of claim 3, wherein the adsorbent is prepared by a method comprising: The application further discloses a preparation method of an adsorbent. Method one: the waste tire is crushed to 8-10 mm, and then pyrolysis is carried out under a nitrogen atmosphere at a heating speed of 15-25 DEG C / min from room temperature to 550-650 DEG C and heat preservation for 0.5-1.5 h to obtain first pyrolysis coke; one or more of water, ethanol and carbon disulfide are used to impregnate the first pyrolysis coke, ultrasonic treatment is carried out after the impregnation is completed, and then drying is carried out at 100-200 DEG C; wherein the impregnation treatment time is 0.5-1.5 h, the ultrasonic treatment power is 800-1200 W, and the ultrasonic treatment time is 5-15 min. Or, Method two: the waste tire is crushed to 8-10 mm, and then pyrolysis is carried out under a nitrogen atmosphere containing 0.1%-1% SO2 gas at a heating speed of 15-25 DEG C / min from room temperature to 550-650 DEG C and heat preservation for 0.5-1.5 h. The adsorbent is prepared by the preparation method.
9. An adsorbent, characterized by, 10. Application of the adsorbent prepared by the preparation method of any one of claims 1-8 in mercury removal and sulfur resistance.
